Staff and student engagement on and perceptions of a college campus’s urban farm - Marc Sager; Lily Binford; Anthony Petrosino (Journal of Agriculture, Food Systems, and Community Development, 2024)
In this commentary, we provide a snapshot into the experiences and perspectives of college students and staff engaged in an on-campus urban farm run by a college. By delving into the challenges faced by staff members and student workers, we seek to identify nuanced areas for improvement in the management, communication, and promotion of the on-campus farm’s work. This commentary emphasizes the imperative to bridge the gap between students and staff, address negative perceptions, and amplify the educational and career value of on-campus farming experiences.